Survey of the presence of Lactobacillus plantarum in the fermented maize dough hydrolysate used in the technology of the improvement of lanhouin - DOSSOU-YOVO, PIERRE; BOKOSSA YAOU, Innocent Padonou; SOPROUNOVA, Olga; EREMEEVA, Svetlana; YELOUASSI, Chimène Aggripine Rodogune (My University, 2012)
Research works are currently going on to find out the real existence of Lactobacillus plantarum in the fermented maize dough hydrolysate and in other fermented maize products in West Africa sub region. This work aims to search for the presence of lactic acid bacteria in general and of the L. plantarum in particular, in fermented maize dough hydrolysate produced in Benin by the fermentation of the maize in water. The use of L. plantarum selective medium (LPSM) denoted the presence of characteristic yellow facultative-anaerobic colonies with a yellow aura in the hydrolysate. This result reveals therefore the presence of L. plantarum which turned around 105 to 106 CFU/ml.
Keywords: Fermented maize dough hydrolysate; lactic acid bacteria; Lactobacillus plantarum.